2015
DOI: 10.1097/ico.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Corneal Sensitivity in Dry Eye Syndromes—A Longitudinal Pilot Study

Abstract: Our results showed diminished CoS in severe dry eye although there was a high variability of CoS. This supports the hypothesis of different states of compensation as the disease continues and an association of CoS with different causes of dry eye. However, no statistical differences were found between etiological subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…A longitudinal study of corneal sensitivity in patients with DES found that, notwithstanding highly variable results, corneal sensitivity was found to be lowered in severe dry eye 37 . Bourcier and coauthors also found that subjects with dry eye can have reduced mechanical, chemical and corneal thermal sensitivity 26 .…”
Section: Regulation Of Basal Tear Production and Lacrimationmentioning
confidence: 99%
See 3 more Smart Citations
“…A longitudinal study of corneal sensitivity in patients with DES found that, notwithstanding highly variable results, corneal sensitivity was found to be lowered in severe dry eye 37 . Bourcier and coauthors also found that subjects with dry eye can have reduced mechanical, chemical and corneal thermal sensitivity 26 .…”
Section: Regulation Of Basal Tear Production and Lacrimationmentioning
confidence: 99%
“…Apart from ageing-related reduced corneal sensitivity, 36 dry eye symptoms may be accompanied by a decrease in corneal sensitivity such as may be associated with refractive surgery, diabetes 18 . herpetic keratitis, topical pharmacological agents and long-term contact lens wear 37 . In addition, dry eye-induced alterations to the properties of corneal afferent neurons and the central processing of corneal input may have significant consequences for both the regulation of tearing and ocular pain 18 …”
Section: Regulation Of Basal Tear Production and Lacrimationmentioning
confidence: 99%
See 2 more Smart Citations
“…While subject numbers are frequently low in individual studies, corneal sensitivity to a pure mechanical stimulus, such as the Cochet Bonnet instrument, is consistently reduced in DED [372,447453]. Of the different subclasses of DED patients, those presumed as demonstrating aqueous deficient DED consistently present with reduced corneal sensitivity using the Cochet Bonnet instrument, and this has been attributed to the greater corneal epithelial disruption assessed by corneal staining [454].…”
Section: Evaluation Of Ocular Surface Neurobiologymentioning
confidence: 99%